Activity-Based Concept to Screen Biological Matrices for Opiates and (Synthetic) Opioids. (1st August 2018) - Cannaert, Annelies; Vasudevan, Lakshmi; Friscia, Melissa; Mohr, Amanda L A; Wille, Sarah M R; Stove, Christophe P
Abstract: BACKGROUND: Detection of new highly potent synthetic opioids is challenging as new compounds enter the market. Here we present a novel screening method for the detection of opiates and (synthetic) opioids based on their activity. METHODS: A cell-based system was set up in which activation of the μ-opioid receptor (MOR) led to recruitment of β-arrestin 2, resulting in functional complementation of a split NanoLuc luciferase and allowing readout via bioluminescence. Assay performance was evaluated on 107 postmortem blood samples. Blood (500 μL) was extracted via solid-phase extraction. Following evaporation and reconstitution in 100 μL of Opti-MEM ® I, 20 μL was analyzed in the bioassay. RESULTS: In 8 samples containing synthetic opioids, in which no positive signal was obtained in the bioassay, quadrupole time-of-flight mass spectrometry revealed the MOR antagonist naloxone, which can prevent receptor activation. Hence, further evaluation did not include these samples. For U-47700 (74.5–547 ng/mL) and furanyl fentanyl (<1–38.8 ng/mL), detection was 100% (8/8) for U-47700 and 95% (21/22) for furanyl fentanyl. An analytical specificity of 93% (55/59) was obtained for the opioid negatives. From an additional 10 samples found to contain other opioids, 5 were correctly scored positive. Nondetection in 5 cases could be explained by very low concentrations (<1 ng/mL alfentanil/sufentanil) or presence of inactive enantiomers. CONCLUSIONS: The MOR reporter assay allows rapid identification of opioid activity in blood. Although the cooccurrence of opioid antagonists is currently a limitation, the bioassay's high detection capability, specificity, and untargeted nature may render it a useful first-line screening tool to investigate potential opioid intoxications.